Combination Therapy of PTH and Antiresorptive Drugs on Osteoporosis: A Review of Treatment Alternatives - Zhang, Chenggui; Song, Chunli (Frontiers in Pharmacology, 2021)
Antiresorptive drugs have been widely used for osteoporosis. Intermittent parathyroid hormone (PTH), an anabolic agent, increases osteoblast production rate and inhibits apoptosis of osteoblasts, thus increasing skeletal mass besides improving bone microarchitecture and strength. Combination therapy for osteoporosis produced great interests and controversies. Therefore, we performed a systematic literature search from PubMed, EMBASE, Scopus, Web of Science, CINDHL, and the Cochrane Database of Systematic Reviews using the search terms PTH or teriparatide combined with bisphosphonate, alendronate, ibandronate, risedronate, raloxifene, denosumab, and zoledronic acid with the limit osteoporosis. At last, 36 related articles were included for further analysis. Findings from previous studies revealed that combination therapy in different conditions of naive or previous bisphosphonate treatment might have different outcomes. The use of combination therapy, however, may be an alternative option among osteoporotic patients with a history of bisphosphonate use. Combined teriparatide with denosumab appear to show the most substantial and clinically relevant skeletal benefits to osteoporotic patients. Additional research is necessary to define optimal methods of developing sequential and/or cyclical combinations of PTH and antiresorptive agents.